2005
DOI: 10.1002/art.21343
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the kinetics of osteoclastogenesis in arthritic rats

Abstract: Objective. To analyze the kinetics of osteoclastogenesis in 2 models of chronic immune-mediated arthritis and 1 model of acute arthritis.Methods. Adjuvant-induced arthritis (AIA) and collagen-induced arthritis (CIA) in Lewis rats were used as models of chronic arthritis. Acute arthritis was induced in Lewis rats by injecting carrageenan into the hind paw. Osteoclasts were identified by cathepsin K immunohistochemistry at various time points after the onset of arthritis. The location, size, and nucleation of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 31 publications
3
41
1
1
Order By: Relevance
“…It has been reported that osteoclast development is enhanced in CIA [44]. Our data demonstrate that GSPE suppresses osteoclastogenesis in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 51%
“…It has been reported that osteoclast development is enhanced in CIA [44]. Our data demonstrate that GSPE suppresses osteoclastogenesis in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 51%
“…Formation of osteoclasts and their precursor cells is thus rapid, early, and triggered by continuous cytokine production and cell influx. In accordance with this, kinetic analyses of osteoclast formation in animal models of arthritis have revealed that cells form only a few days after the onset of inflammation [29]. …”
Section: Rankl In Arthritismentioning
confidence: 75%
“…The presence and activation of osteoclasts seem to be involved in the pathogenesis of OA and other cartilage-destructive diseases, such as RA, psoriasis arthritis149 and spondyloarthropathies 120 121 150. Does this suggest that interventions that reduce bone turnover may have secondary positive effects on the progression of OA?…”
Section: Targeting Bone and Cartilage In The Treatment Of Oamentioning
confidence: 99%